Tourists' behaviors and evaluations - Woodside, Arch G.; Kozak, M. 1968- (Emerald, 2014)
The authors propose that complexity theory holds great promise in improving understanding of guests evaluations of their service experiences. Volume 9 provides answers to the following and additional behavior and evaluation issues. How do general and behavior specific attitudes work together in explaining air travelers carbon offsetting behavior? What can the zone of tolerance and importance-performance analysis (IPA) techniques tell us about the evaluations of convention delegates perceptions of products and services? How can a œslow city motivate domestic tourists to visit the destination? Do effective marketing strategies for performing arts require unique designs to attract incidental spectators as well as behaviourally loyal visitors? When do consumers attach themselves strongly to tourist souvenirs as well as to other cherished possessions such as a trophy won during a contest, a gift received from significant others, or a wedding ring? What are the nitty-gritty details in how exhibition areas can provide visitors with opportunities to understand corporate brands? Since values influence activities do they also influence holiday preferences?
Keywords: Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Hospitality industry.; Tourism industry.; Tourism -- Research.; elektronické knihy; electronic books